Una aproximación a las definiciones, tipologías y marcos teóricos de la migración de retorno - Jáuregui Díaz, José Alfredo; Recaño Valverde, Joaquín (Universidad de Barcelona, 2014)
Return migration is considered a special case of a migration, however their study is not a simple issue, and depending on the historical moment and place of occurrence it has specificities that need to be known as well as their recurrent characteristics. The international migration provides an excellent framework that permit to explain the main characteristics and the principal typologies of return migration. This paper examines the theoretical background and the different ways that return migration has been defined from the point of view of three social sciences: Economics, Sociology and Demography.